THE IMPACT OF STRAWBERRY GENERATION LABELING ON SELF-RESILIENCE AND INTERGENERATIONAL COMMUNICATION - Rizky Jagad Dito Pratisco; Ahmad Subekti (Universitas Muhammadiyah Jakarta, 2026)
This study investigates the impact of the